Influence Of Bank Health Level On Stock Return - Wardyaningrum, Elisabeth Winda Putri; Murti, Galuh Tresna (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The main objective of this research is to assess the correlation between the soundness of banks and their stock returns. The investigation encompasses 39 banking firms that are publicly traded on the Indonesian stock exchange throughout the time span from 2018 to 2021. A quantitative approach is employed, involving the use of descriptive analysis for panel data. The findings indicate that the amalgamation of NPL, GCG, ROA, and CAR collectively exert an influence on stock returns. However, it's noteworthy that only the ROA and CAR variables exhibit a distinct partial impact on stock returns. The conclusions drawn from this study encompass a few implications. One of them is the anticipation for banking institutions to effectively optimize and elevate their health status, consequently leading to an enhancement in the returns of banking stocks. From an investor's perspective, this research serves as a pertinent factor to weigh when making investment decisions, by examining internal dynamics of companies, which are some of the pivotal elements steering stock returns.